Fatty acid intercalated layered double hydroxides as additives for Jojoba oil and polymer matrices - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2013)
Thesis (PhD(Eng))--University of Pretoria, 2012.